2021
DOI: 10.1016/j.cels.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive prediction of robust synthetic lethality between paralog pairs in cancer cell lines

Abstract: Highlights d Dual CRISPR screens have identified mainly context-specific paralog synthetic lethals d We identified 22 features predictive of robust synthetic lethality between paralogs d Developed a classifier to make interpretable predictions of paralog synthetic lethality d Experimentally validated synthetic lethality between ASF1A/ ASF1B and COPS7A/COPS7B

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 103 publications
4
73
0
Order By: Relevance
“…Other well described synthetic lethal cases include RPP25L/RPP25 16 18 , CDS2/CDS1 16 (Table 1 ) as well as other high C-score gene pairs, UAP1/UAP1L1 16 , 19 , 20 , SMARC4/SMARC2 16 , 18 , 20 , 21 , and ENO1/ENO2 22 (Supplementary Table S1 ). Comparing with nine other predictions of synthetic lethality 23 31 to four larger scale studies of experimental evidences 16 , 19 , 20 , 32 , the high C-score gene pairs demonstrated among the highest number of matches to experiments, even though matches between prediction to experiments remains few (0 to 14.3%, Supplementary Table S2 ). This result indicate identification of buffering and synthetic lethality is non-trivial, possibly due to a wide variety of biological mechanisms, and the CEBU concept may be one of these mechanisms.…”
Section: Resultsmentioning
confidence: 97%
“…Other well described synthetic lethal cases include RPP25L/RPP25 16 18 , CDS2/CDS1 16 (Table 1 ) as well as other high C-score gene pairs, UAP1/UAP1L1 16 , 19 , 20 , SMARC4/SMARC2 16 , 18 , 20 , 21 , and ENO1/ENO2 22 (Supplementary Table S1 ). Comparing with nine other predictions of synthetic lethality 23 31 to four larger scale studies of experimental evidences 16 , 19 , 20 , 32 , the high C-score gene pairs demonstrated among the highest number of matches to experiments, even though matches between prediction to experiments remains few (0 to 14.3%, Supplementary Table S2 ). This result indicate identification of buffering and synthetic lethality is non-trivial, possibly due to a wide variety of biological mechanisms, and the CEBU concept may be one of these mechanisms.…”
Section: Resultsmentioning
confidence: 97%
“…Again, we observe that not all screens can identify members of this complex as essential. In this complex, we don't observe COPS7A and COPS7B as essential in any screen since, as we and others have previously shown, COPS7A and COPS7B are synthetic lethal paralog pairs and they encode alternate, replaceable subunits of the complex, while the other subunits are irreplaceable and are uniformly essential (De Kegel et al, 2021;Dede et al, 2020).…”
Section: False Negatives Are Evident In Essential Protein Complexesmentioning
confidence: 72%
“…Specifically, we found that genes from larger paralog families and genes with a more sequence similar paralog are more likely to be dispensable -presumably because those properties can be linked to increased buffering capacity for paralog loss. We also found that paralogs that originated from a whole genome duplication (WGD) as opposed to a small scale duplication (SSD) were both more likely to be essential at least some of the time, but less likely to be essential all of the time -this could be explained by WGD paralogs being more likely to be synthetic lethal (De Kegel et al, 2021;De Kegel & Ryan, 2019). Having determined that paralog passenger genes are overall more likely to be homozygously deleted in tumors, we next asked whether there are differences in the deletion frequency of paralogs with different properties.…”
Section: Homozygous Deletion Frequency Of Paralog Passengers Is Influ...mentioning
confidence: 84%
“…To identify broadly essential genes from the DepMap CRISPR screens we used the gene dependency scores from (Table S2, (De Kegel et al , 2021)). These gene dependency scores were computed with CERES (Meyers et al , 2017) after filtering out potential multi-targeting single guide RNAs, which disproportionately affect paralog dependency scores.…”
Section: Methodsmentioning
confidence: 99%